Rancang Bangun Aplikasi Pelaporan Proyek Pembangunan Pada PT Dua Daya Sakti - Irsajidin, Muhammad; Wurijanto, Tutut; Koentjoro, Edo Yonatan (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
PT Dua Daya Sakti is a company engaged in the field of property developers, special housing clusters located in Gresik. One of the company's mission goals is to provide the best service and prioritize customer satisfaction by fully supporting work on time. Before starting the development project, first make a Budget plan. The Budget Plan is used as a standard or benchmark for managing existing compilations. Every project development activity, planning planning must study each project development to check the costs incurred according to plan or not. Every project development process will be reported and made manually so that there is a delay in helping information about the project's progress.Based on these considerations, it is necessary to have an application that can assist project reporting. The project reporting application uses the cost analysis method where plans and evaluations will be compared.The test results show that the application can make a report on the difference in time and cost of the project that has been done with a predetermined plan. Related to the ease of project owners to see the time and costs that have been realizedÂ Keywords:Â Application, Project Reporting, Property